(untitled) (Research, Society and Development, 2023)
COVID-19 has brought numerous challenges for the dairy industry. This research aimed to analyze the impact of the COVID-19 pandemic on Brazilian dairy cattle farming. The study was conducted from December 2020 to February 2021 via Google Forms® platform. Data obtained were tabulated and evaluated using descriptive and multivariate analysis, Shapiro-Wilk, Kruskall-Wallis, Variance Analysis (ANOVA), and Dunn’s post-hoc comparison. The study was approved by the Committee for Ethics in Research with Human. In total, 73 viable responses were obtained, with participations from the Brazilian regions Midwest, Northeast, South, and Southeast. Among the biosecurity measures adopted during the study, 86% of farm employees began to sanitize their hands more often to prevent the transmission of COVID-19. Use of masks during work was required all the time during work by employees in 17 properties (23%), although the use of masks was not required in 40 (55%) farms and 16 properties required them during part of the work (22%). Regarding milk production, 99% of the respondents had no problems with milk collection and more than half of the producers had difficulties in acquiring animals. Moreover, thirty-seven percent of the interviewees said they were unaware of how the virus was transmitted. Regarding the size of the dairy farms, small farms were more likely to have no veterinary medical care. The pandemic brought positive and negative impacts to dairy properties, which was influenced by the number of animals, the presence of veterinary care, and average daily milk production.